2012
DOI: 10.1038/nrneurol.2012.170
|View full text |Cite
|
Sign up to set email alerts
|

Prism adaptation for spatial neglect after stroke: translational practice gaps

Abstract: Spatial neglect increases hospital morbidity and costs in around 50% of the 795,000 people per year in the USA who survive stroke, and an urgent need exists to reduce the care burden of this condition. However, effective acute treatment for neglect has been elusive. In this article, we review 48 studies of a treatment of intense neuroscience interest: prism adaptation training. Due to its effects on spatial motor ‘aiming’, prism adaptation training may act to reduce neglect-related disability. However, researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
1
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 99 publications
2
63
1
8
Order By: Relevance
“…Dos indivíduos com heminegligência visual, 11 (79%) eram do sexo masculino, com média de idade de 62,9 ±12,0 anos e a média do tempo de internamento foi 11,2 ±10,5. Oito (57%) tiveram AVC isquêmico, oito (57%) lesão no hemisfério esquerdo, a mediana da gravidade do AVC foi 8 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), da incapacidade foi 1,2 (1)(2)(3)(4)(5). Dos indivíduos com heminegligência visual e tátil, três (60%) eram homens, mais velhos 68,0 ±15,6, três (60%) tiveram AVC isquêmico e três (60%) a lesão no hemisfério direito e tempo de internamento de 13,3 ±6,8 dias, com mediana da gravidade do AVC 8 (7)(8)(9)(10)(11)(12)(13)(14) e da incapacidade 5 (1-5) pontos.…”
Section: Resumo | Introduçãounclassified
See 2 more Smart Citations
“…Dos indivíduos com heminegligência visual, 11 (79%) eram do sexo masculino, com média de idade de 62,9 ±12,0 anos e a média do tempo de internamento foi 11,2 ±10,5. Oito (57%) tiveram AVC isquêmico, oito (57%) lesão no hemisfério esquerdo, a mediana da gravidade do AVC foi 8 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), da incapacidade foi 1,2 (1)(2)(3)(4)(5). Dos indivíduos com heminegligência visual e tátil, três (60%) eram homens, mais velhos 68,0 ±15,6, três (60%) tiveram AVC isquêmico e três (60%) a lesão no hemisfério direito e tempo de internamento de 13,3 ±6,8 dias, com mediana da gravidade do AVC 8 (7)(8)(9)(10)(11)(12)(13)(14) e da incapacidade 5 (1-5) pontos.…”
Section: Resumo | Introduçãounclassified
“…Dentre as alterações que ocorrem após o AVC a hemiparesia é um dos déficits mais perceptíveis após o evento, se caracterizando por mudanças neurológicas, sensoriais, alterações na ativação muscular e recrutamento de unidades motoras 2 . Neste contexto, existe a heminegligência, estando entre as sequelas com pior prognóstico, se caracteriza como uma alteração perceptual onde o indivíduo não produz respostas aos estímulos contralaterais ao hemisfério cerebral lesionado 3,4 . Nessa condição, o indivíduo negligencia o hemicorpo comprometido, impactando diretamente a sua funcionalidade, restringindo a execução das Atividades de Vida Diária (AVD) relacionadas à alimentação, higiene pessoal e mobilidade, limitando a independência 3,5 .…”
Section: Resumo | Introduçãounclassified
See 1 more Smart Citation
“…Various reviews on PA as a treatment method for neglect have been published recently (specifically Barrett et al, 2012;Newport and Schenk, 2012;Jacquin-Courtois et al, 2013). In each of these reviews, it is concluded that PA might be an effective therapy for patients with neglect.…”
Section: Prism Adaptationmentioning
confidence: 99%
“…In each of these reviews, it is concluded that PA might be an effective therapy for patients with neglect. However, Barrett et al (2012) emphasize that PA is not yet ready for broad administration in stroke rehabilitation and that it might be applied specifically for subgroups of patients presenting with motor-intentional "aiming" deficits. Newport and Schenk (2012) conclude that PA is only effective if training consists of 10 or more PA sessions.…”
Section: Prism Adaptationmentioning
confidence: 99%